Penerapan cognitive behavior therapy untuk mengatasi gangguan cemas menyeluruh - Fadillah, Atina Okta; Pranungsari, Dessy (Universitas Ciputra Surabaya, 2024)
Generalized anxiety disorder (GAD) is generalized and persistent anxiety that is not limited to certain situations. Individuals who experience GAD will certainly have obstacles in their daily activities. The purpose of this study is to determine the success of the application of CBT (cognitive behavior therapy) to individuals who experiencing GAD. The research method in this study was quantitative approach with single case pre test-post test design. Participant was a woman who experienced GAD. Data were collected using observation, interview, and psychological test. Measurement of GAD using GAD-7. The intervention in this study using CBT with mind over mood technique. The intervention was given for 5 meetings. There was a decrease score on the subject, before being given CBT the GAD-7 score was 14 (moderate) and after being given CBT the subject's GAD-7 score dropped to 2 (normal). The results of this study indicate that CBT is able to overcome the generalized anxiety disorder experienced.